Φ admissibility of linear estimators of common mean parameter in general multivariate linear models under a balanced loss function. Issue 17 (9th August 2021) - Cao, Mingxiang; Park, Junyong; Shen, Guangjun
Abstract: The definitions of Φ optimality and Φ admissibility of matrix common mean parameter are given in general multivariate linear models under a generalized matrix balanced loss function. We extend some previous studies to more general cases such that Φ admissibility of linear estimators on matrix common mean parameter. Sufficient and necessary conditions for linear estimators to be Φ admissible are obtained in classes of homogeneous and non homogeneous linear estimators, respectively.